The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s00526-021-02040-3
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of Darcy’s law in randomly perforated domains

Abstract: We consider the homogenization of a Poisson problem or a Stokes system in a randomly punctured domain with Dirichlet boundary conditions. We assume that the holes are spherical and have random centres and radii. We impose that the average distance between the balls is of size $$\varepsilon $$ ε and their average radius is $$\varepsilon ^{\alpha }$$ ε α , $$\alpha \in (1; 3)$$ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This condition was removed by Giunti and Höfer [10], where they showed that for incompressible fluids and randomly distributed holes with random radii, the randomness does not affect the convergence to Brinkman's law. More recently, for large particles, Giunti showed in [9] a similar convergence result to Darcy's law.…”
Section: Introductionmentioning
confidence: 63%
“…This condition was removed by Giunti and Höfer [10], where they showed that for incompressible fluids and randomly distributed holes with random radii, the randomness does not affect the convergence to Brinkman's law. More recently, for large particles, Giunti showed in [9] a similar convergence result to Darcy's law.…”
Section: Introductionmentioning
confidence: 63%
“…This condition was removed by Giunti and Höfer [12], were they showed that for incompressible fluids and randomly distributed holes with random radii, the randomness does not affect the convergence to Brinkman's law. More recently, for large particles, Giunti showed in [10] a similar convergence result to Darcy's law.…”
Section: Introductionmentioning
confidence: 63%
“…In terms of the related research topics, to the authors' best knowledge, the pioneer literatures were contributed by E. Marušić-Paloka, A. Mikelić, L. Paoli [30,33], where they obtained a rate O(ε 1 6 ) for steady Stokes problems and an error O(ε) for non-stationary incompressible Euler's equations, respectively, in the case of d = 2. Homogenization and porous media have been received many studies, without attempting to be exhaustive, we refer the reader to [1,5,9,10,11,12,13,14,19,18,23,24,27,38,42,43,46,50] and the references therein for more results. 7 In stationary case, the same extension could be found in [3,26], and it played a similar role in the qualitative theory for the unsteady case presented by [2,4,31].…”
Section: Motivation and Main Resultsmentioning
confidence: 99%